Volcano hazard and surveillance in Costa Rica - Avard, Geoffroy (2021)
Costa Rica hosts ten volcanic complexes and is highly tectonically active due to its location at the interaction between the Cocos, Nazca, and Caribbean plates and the Panama microplate. Three of the five historically active volcanoes had frequent eruptions in 2019. The institutions in charge of monitoring the volcanoes of Costa Rica are the Observatorio Vulcanológico y Sismológico de Costa Rica from Universidad Nacional (OVSICORI-UNA) and the Red Sismológica Nacional (RSN: UCR-ICE that groups the Escuela Centroamericana de Geología from the Universidad de Costa Rica, and the Observatorio Sismológico y Vulcanológico de Arenal y Miravalles from the Instituto Costarricense de Electricidad; acronyms ECG, UCR, OSIVAM, and ICE). These institutions are focused on the most dangerous volcanoes, i.e. those closest to the Great Metropolitan Area (2.2 million inhabitants), which includes San José (the capital), and those near hydroelectrical and geothermal plants. In 2020, those institutions operated a network of. 59 seismic stations on volcanoes, 5 infrasound stations, 25 permanent GPS sites, 2 permanent DOAS, 3 permanent MultiGAS, 13 webcams, and performed systematic analyses in geochemistry and petrology laboratories. Those institutes routinely communicate results with the authorities in charge of crisis management nationally and internationally (Comisión Nacional de Prevención de Riesgos y Atención de Emergencias and Volcanic Ash Advisory Centre, respectively) and are always looking for more scientific collaborations.